Hemoglobin A1c (HbA1c) Levels from the Examination of Different Blood Proportions in K2EDTA Tubes using an Enzymatic Method - , Museyaroh; Nabilah, Musholli Himmatun; Werdiningsih, Retno (Folia Medica Indonesiana, 2023)
Highlights: 1. Research on the effect of blood volume proportion in the examination of HbA1c levels using K2EDTA anticoagulantvhas yet to be widely carried out in Indonesia. 2. The analysis conducted utilizing K2EDTA tubes revealed that the varying proportions of blood samples had no effectvon HbA1c levels. 3. This article highlights the necessity of evaluating the pre-analytical phase (sample preparation) of a laboratory process to improve the accuracy of the results and minimize false high or low results in the HbA1c test. Abstract Hemoglobin A1c (HbA1c) examination is the gold standard for diagnosing and monitoring diabetes mellitus patients. In the examination, the pre-analytical phase has the most considerable error rate at 61%. One of the contributing factors is the use of anticoagulants that do not adhere to established guidelines. Additionally, the incompatibility of the sample volume proportions and the anticoagulants in K2EDTA tubes has been observed in numerous cases. The significance of HbA1c testing, particularly in the prevention of diabetes complications, underscores the need for appropriate procedures to be followed throughout the sampling and pre-analytical phases. This study aimed to determine the effect of differences in the proportion of blood sample volume and anticoagulants in K2EDTA tubes on HbA1c levels. This research was conducted in August–September 2022. The research samples were collected from the staff and students at the Department of Medical Laboratory Technology, Politeknik Kesehatan Kemenkes Surabaya, Surabaya, Indonesia. The blood samples were divided into K2EDTA tubes with varying volumes of 1 mL, 2 mL, 3 mL, and 4 mL. The HbA1c levels were then examined at the Clinical Chemistry Laboratory of Politeknik Kesehatan Kemenkes Surabaya. The data were analyzed using a one-way ANOVA test. The statistical test results (p>0.05) indicated that the proportion of samples containing anticoagulants in the K2EDTA tubes did not have any significant effect on HbA1c levels. In conclusion, it is acceptable to utilize K2EDTA tubes with varying blood sample volumes for the measurement of HbA1c levels.